Board Size Determinants: Evidence from Nigeria - Badru, Bazeet Olayemi; Davies, Nordiana Osagie; Abdulkadir, Rihanat Idowu (UUM Press, 2020)
This paper seeks to investigate the determinants of board size for Nigerian companies. To accomplish the aim of the study, a panel data set of public listed companies in Nigeria from 2005 to 2015 was employed. The results showed that the most common board size of Nigerian companies ranged from four to 18 members. Specifically, the findings indicated that board size was a function of company and industry characteristics. A significant and positive association was found between company size and board size, while CEO ownership and ownership concentration were negative. The results lend support to theoretical arguments that a companys board structure is determined by the scope of company operations and monitoring costs associated with the company. Since company-specific characteristics determine board size, the impact of board size on corporate outcomes may differ based on these characteristics. Therefore, it would be helpful if future studies could consider the interactive effect of company characteristics when investigating the impact of board size on corporate outcomes.